Carotid‐Access Transcatheter Aortic Valve Replacement in a Patient with a Previous Mitral Valve Replacement. Issue 3 (10th March 2014) - Daly, Michael J.; Blair, Paul H.; Modine, Thomas; Donnelly, Patrick M.; Jeganathan, Reuben; Manoharan, Ganesh; Spence, Mark S.
Abstract We describe a case of transcatheter aortic valve replacement (TAVR) using carotid artery access and regional anesthesia in a patient with rheumatic heart disease, previous mitral valve replacement, and multiple co‐morbidities. It highlights the role of the multidisciplinary Heart Team and multimodality imaging in reaching and implementing an appropriate management plan in this complex patient group. doi: 10.1111/jocs.12324 (J Card Surg 2015;30:256–259)